Clinical management of persistent gingival bleeding induced by the combination of multiple anticoagulant drugs: A case report and literature review - JIN Lei; XUE Chao; WANG Shimei; CAI Weixin (Kouqiang hemian waike zazhi)
[Objective:] To retrospectively analyse a case of uncontrollable bleeding after supragingival scaling that occurred in May 2023 at the People's Hospital of Fengqing County, Yunnan Province. The prevention and management of uncontrollable bleeding caused by systemic factors after invasive oral procedures were discussed. [Methods:] A multidisciplinary consultation was conducted with the cardiology, pharmacy, and hematology-endocrinology departments. Local treatment included the application of levonordefrin tartrate and cold saline. Intravenous administration of vitamin K and tranexamic acid was also provided. [Results:] Hemostasis was achieved locally within 48 hours after admission. The patient's vital signs stabilized, and follow-up laboratory examinations showed no significant abnormalities. [Conclusion:] A thorough inquiry into the patient's medical history is essential before performing invasive oral procedures. For patients on long-term anticoagulant therapy, particularly those using multiple anticoagulants, multidisciplinary consultations can effectively guide treatment and reduce the risk of postoperative bleeding.